Web-based Development of Taska Khairiyyah Wafiq Management System - Sithambranathan, Haamsevani; Mat Nawi, Rosmamalmi (Applied Information Technology And Computer Science, 2023)
Taska Khairiyyah Wafiq Management System (TKWMS) is a web-based system and it is developed especially for administrators, teachers and parents of Taska Khairiyyah Wafiq. This project is being put up as a solution to the significant issue of manually entering and maintaining staff and children information using traditional method like paper, pen, and files. As a result, the study’s aim is to propose and develop a new web-based management system for Taska Khairiyyah Wafiq. Therefore, the system is anticipated to record properly every crucial detail into the system so that it is easy, fast and efficient for the users to carry out their tasks into the system. The system consists of children details, children development progress, children overtime care, teacher details, teacher overtime care and payment. The project was created using an Agile software development model, which involves continuous improvement.